Investigating dynamic relations between factual information and misinformation: Empirical studies of tweets related to prevention measures during COVID‐19. (18th November 2021) - Wang, Yan; Gao, Shangde; Gao, Wenyu
Abstract: During COVID‐19, misinformation on social media has affected people's adoption of appropriate prevention behaviors. Although an array of approaches have been proposed to suppress misinformation, few have investigated the role of disseminating factual information during crises. None has examined its effect on suppressing misinformation quantitatively using longitudinal social media data. Therefore, this study investigates the temporal correlations between factual information and misinformation, and intends to answer whether previously predominant factual information can suppress misinformation. It focuses on two prevention measures, that is, wearing masks and social distancing, using tweets collected from April 3 to June 30, 2020, in the United States. We trained support vector machine classifiers to retrieve relevant tweets and classify tweets containing factual information and misinformation for each topic concerning the prevention measures' effects. Based on cross‐correlation analyses of factual and misinformation time series for both topics, we find that the previously predominant factual information leads the decrease of misinformation (i.e., suppression) with a time lag. The research findings provide empirical understandings of dynamic relations between misinformation and factual information in complex online environments and suggest practical strategies for future misinformation management during crises and emergencies.